Mindfulness Training Improves Quality of Life and Reduces Depression and Anxiety Symptoms Among Police Officers: Results From the POLICE Study—A Multicenter Randomized Controlled Trial - Trombka, Marcelo; Demarzo, Marcelo; Campos, Daniel; Antonio, Sonia B.; Cicuto, Karen; Walcher, Ana L.; García-Campayo, Javier; Schuman-Olivier, Zev; Rocha, Neusa S. (Frontiers in Psychiatry, 2021)
Background: Police officers’ high-stress levels and its deleterious consequences are raising awareness to an epidemic of mental health problems and quality of life (QOL) impairment. There is a growing evidence that Mindfulness-Based Interventions are efficacious to promote mental health and well-being among high-stress occupations. Methods: The POLICE study is a multicenter randomized controlled trial (RCT) with three assessment points (baseline, post-intervention and six-month follow-up) where police officers were randomized to Mindfulness-Based Health Promotion (MBHP) (n=88) or a waiting list (n=82). This manuscript focus on QOL, depression and anxiety symptoms, and religiosity outcomes. Mechanisms of change and MBHP feasibility were evaluated. Results: Significant Group x Time interaction was found for QOL; depression and anxiety symptoms; and non-organizational religiosity. Between-groups analysis showed that MBHP group exhibited greater improvements in QOL, depression and anxiety symptoms at both post-intervention (QOL d=.69 to 1.01; depression d=.97; anxiety d=.73) and six-month follow-up (QOL d=.41 to .74; depression d=.60; anxiety d=.51); in addition to increasing non-organizational religiosity at post-intervention (d=.31). Changes on self-compassion mediated the relationship between group and pre-to-post changes for all QOL domains and facets. Group effect on QOL overall health facet at post-intervention was moderated by mindfulness trait and spirituality changes. Conclusion: MBHP is feasible and efficacious to improve QOL, depression and anxiety symptoms among Brazilian officers. Results were maintained after 6 months. MBHP increased non-organizational religiosity, although the effect was not sustained 6 months later. To our knowledge, this is the first Mindfulness-Based Intervention RCT to empirically demonstrate these effects among police officers. Self-compassion, mindfulness trait and spirituality mechanisms of change are examined. Trial registration: ClinicalTrials.gov NCT03114605